Fitness Training As a Body-Centered Hobby: the Serious Leisure Perspective for Explaining Exercise Practice - Codina, Nuria; Vicente Pestana, José; A Stebbins, Robert (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
Physical exercise is an activity whose health-related benefits have been promoted by health professionals and social institutions. However, given that the levels of practice are not ideal, the subjective variables – that give meaning, provide continuity and may increase exercise adherence – need to be studied in depth. In this sense, fitness training is analyzed as a form of serious leisure, a body-centered hobby – a way to practice and relate to the activity that leads its practitioners to adhere more to it, orienting them towards a career in acquiring and expressing skills, knowledge and experience. In total, 1,134 people (588 men, 546 women) doing fitness training, aged between 18 and 70 years old (M = 34.7, SD = 13.06), answered a questionnaire about time dedicated to exercise as serious leisure and its derived and complementary benefits. Student’s t Coefficient and ANOVA were used to show the significance of the differences among the scores obtained for the rewards related to exercise and the other variables of the study. The results highlight that exercise as serious leisure is an activity whose weekly time investment makes it to acquire a central role when rewarded by sense of accomplishment, contact with others, improved health and being outdoors with the family. To conclude, this study enhances that characterizing fitness training as a body-centered hobby – which shares the principles of serious leisure – implies a new approach to the analysis of exercise while also suggesting new ways of promoting it.